Study of Caisson Foundation Planning for Bridge Abutments: A Case of Aifa Bridge Abutment in Fafurwar Bintuni Bay, West Papua Province - Ferdinand Ferdinand; Mohamad Taufik (LEADER: Civil Engineering and Architecture Journal, 2023)
The country's growing population and economic development have led to an increased demand for transportation infrastructure. The bridge's main components, including the superstructure, substructure, and foundation, are explained. The focus is on the bridge abutment, which plays a crucial role in supporting the bridge and transmitting loads to the foundation.In geotechnical engineering, caisson foundations play a vital role in supporting structures, especially in areas with weak or unstable soil conditions. To plan for these foundations, a quantitative research approach is used, which includes collecting both primary and secondary data. The primary data is gathered from the study site, while the secondary data consists of literature, articles, journals, and previous research projects. In this case, the data used for planning the caisson foundation came from an earlier Final Project by Muhammad Yunus on the stability analysis of a bridge abutment in West Papua Province. After analyzing the caisson foundation for the bridge, it was found that it meets the necessary safety requirements. The Factor of safety was calculated and resulted in a value of 1.618, which is higher than the minimum acceptable value of 1.5. Therefore, the foundation is capable of bearing the load of the bridge and the weight of the caisson without experiencing failure or excessive settlement.